The critique of theological reason - Mackey, James Patrick (Cambridge University Press, 2000)
This book attempts to describe the nature and prospects of Christian theology in a postmodern era. It takes the best of modern scientific theory about the nature and end of the universe and the best of contemporary Christian theology, and outlines a philosophically viable theology for today's evolutionary world.